BOOKS: Colors of Enchantment: Theater, Dance, Music, and the Visual Arts of the Middle East - Amit-Kochavi, Hannah (Hagar: Studies in Society and Culture, 2002)
Edited by Sherifa Zuhur, The American University in Cairo Press 2001, 456 pp.